Models of measurement and disclosure of fair value accounting - Applied to contribute to company garments mixed - سلمان عامر محمد; عوجة حسنين كاظم (Journal of Economics and Administrative Sciences, 2012)
The research aims to provide a method to measure the fair value of the most environmentally friendly of Iraq and through the application of method of measuring the fair value of the company garments contribute to mixed as the company is of the economic units of the industrial sector and included in the Iraqi market for securities as a profit and distributes profits to shareholders since the method of measurement of the fair value based on the divided profits as toxic in a deduction of Cash Dividends cash for measuring fair value, and will also be in this research to clarify the disclosure of accounting for fair value and choose the method of disclosure most appropriate to the beneficiaries of accounting disclosure, as will be chosen method statements additional to financial statements, the statement of the reasons for the interest at fair value and the appropriateness of fair value in the decision-making, research found that the fair value of one of the measures most appropriate to take decisions and also that the principle of historical cost is the measure most reliable but it is not appropriate to take decisions because of information that The events provided by the principle of the past, so the information from those historic events.